Cardiovascular outcomes at recommended blood pressure targets in middle-aged and elderly patients with type 2 diabetes mellitus and hypertension. (4th March 2021) - Olsen, Eirik; Holzhauer, Björn; Julius, Stevo; Kjeldsen, Sverre E.; Larstorp, Anne Cecilie K.; Mancia, Giuseppe; Mehlum, Maria H.; Mo, Rune; Rostrup, Morten; Søraas, Camilla L.; Zappe, Dion; Weber, Michael A.
Abstract: Purpose: Available data of event-based clinical outcomes trials show that little evidence supports the guidelines recommendations to lower blood pressure (BP) to <130/80 mmHg in middle-aged and elderly people with type 2 diabetes mellitus and hypertension. We addressed this issue by post-hoc analysing the risk of cardiovascular (CV) events in mostly elderly high-risk hypertensive patients with type 2 diabetes mellitus participating in the Valsartan Antihypertensive Long-term Use Evaluation (VALUE) trial. Material and methods: Patients ( n = 5250) were divided into 4 groups according to the proportion of on-treatment visits before the occurrence of an event (<25% to ≥ 75%) in which BP was reduced to <140/90 or <130/80 mmHg. Results: After adjustment for baseline demographic differences between groups, a reduction in the proportion of visits in which BP achieved <140/90 mmHg accompanied a progressive increase in the risk of CV mortality and morbidity as well as of cause-specific events such as stroke, myocardial infarction and heart failure. A progressive reduction in the proportion of visits in which BP was reduced <130/80 mmHg did not have any effect on CV risks. Conclusion: In mostly elderly high-risk hypertensive patients with type 2 diabetes mellitus participating in the VALUE trial, achieving more frequently BP <140/90 mmHg showed a marked protective effect on overall and all cause-specific cardiovascular outcomes. This was not the case for a more frequent achievement of the more intensive BP target, i.e. <130/80 mmHg.